Geek Girl - Smale, Holly (London HarperCollins Children's Books, 2013)
"My name is Harriet Manners, and I am still a geek." MODEL MISFIT is the sequel to award-winning No. 1 UK debut GEEK GIRL.
Keywords: Teenage girls -- Models (Persons) -- Fashion